Impact Analysis of Cirata Floating PV Integration on Frequency Stability in the 500 KV Java-Bali Grid - Yanuar Wahyu Gianto Yayan; Awan Uji Krismanto; Widodo Pudji Muljanto (Forum Pendidikan Tinggi Teknik Elektro Indonesia (FORTEI), 2025)
Rising global demand for clean energy has accelerated the deployment of renewable energy sources, notably Solar Photovoltaic (PV) systems. The Cirata Floating Solar PV Plant, with an installed capacity of 192 MWp and interconnected to the 500 kV Java-Bali transmission network, represents a key national strategic project aimed at supporting the national energy mix target. However, the integration of inverter-based renewable generation such as PV plants introduces challenges to system frequency stability, primarily due to the absence of rotational inertia contribution. This research analyze the impact of the Cirata Floating Solar PV integration on the frequency stability of the 500 kV Java-Bali power system. The analysis is conducted through time-domain dynamic simulations using DigSILENT PowerFactory software, incorporating load flow and dynamic simulation methodologies under three operating scenarios: load shedding, 50% load bekasi increase, and Tripping of saguling power plant. Key frequency stability indicators, namely frequency nadir and Rate of Change of Frequency (RoCoF), are evaluated. The simulation results indicate a degradation in frequency stability performance following the integration of PV due to reduced system inertia. Nevertheless, under specific operating conditions, the PV plant exhibits a beneficial damping effect on frequency deviations.